Analisis Penerapan Integrasi Budaya Minangkabau dalam Pembelajaran IPAS Kurikulum Merdeka di Sekolah Dasar - Abdul Muin; Niken Wahyu Utami (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research was motivated by the lack of integration of Minangkabau culture in Integrated Science (IPAS) learning at the elementary school level, resulting in knowledge gaps and students' lack of appreciation for their local culture. The aim of this research is to analyze the implementation of Minangkabau cultural integration in science and science learning for fourth grade elementary school students. Qualitative research was conducted using a Minangkabau Culture-Based Learning approach in Elementary Schools. Research findings show that the integration of Minangkabau culture in science learning is achieved through cultural practice activities and the use of regional languages, thereby creating a deep and relevant learning experience for students. The teacher's approach in integrating Minangkabau cultural content enriches students' understanding, fostering interesting and relevant learning experiences. The research concluded that the integration of Minangkabau culture in science and science learning creates a learning environment that is holistic, deep and empowering. This increases students' understanding and appreciation of local culture while instilling a sense of pride in their cultural heritage.